PENGEMBANGAN KAMUS FISIKA BERGAMBAR UNTUK MATERI FISIKA MTSS PLUS BALIMBING KELAS VIII - Murviza, Refni Oktri; Lizelwati, Novia; Trisoni, Ridwal (Jurnal Pembelajaran MIPA, 2014)
The aim of this research is to general result of productÂ  in the from dictionary physics pictorial which can assist student MTsS Plus Balimbing in comprehend term physics while target of research pecullarly is to get data whethet dictionary physics pictorial which result of valid and practical. Solution skripsi this startingÂ  from the root of the matter that is (1)book which available in school and have personally by student still limited, many student which gone off at subject physics because the ganerally assum, physics at difficul and boring. Besides many there are term which doânot understand and less can comprehend them and many formula. (2)Subject physics still centrally at teacher because limitation texbook and source of learn. (3) There is weakness dictionary physics which circulating and marketing one ofÂ  them not yet as according to curriculum and also bearing concept physics with phenomenon that happened around less comprehend student. Over come to problems a bove, teacher the claim to could chosen and determine source learning and source learningÂ  or items study correct in order to assisted student reach interest which expect better student would understand with concept if student following in active find concept and study also will be more have a meaning of to student lesson will interesting if teaching can quide student to find resolving problems and make student active find concept or items lesson self for that require to existence of source learning containing clarification conception as does dictionary physics pictorial there fore in research this researcher would develop dictionary physics to items physics class VIII.Key words: camus, physic,